Hearing loss after noise exposure - Govindaraju, Revadi; Omar, Rahmat; Raman, Rajagopalan; Ramli, Norlisah; Ng, Kwan Hoong (Elsevier, 2011)
The higher field strength magnetic resonance imaging (MRI) such as 3 Tesla (T) and above generates noise that has potential detrimental effects on the hearing. Temporary threshold shifts following MRI examination have been reported for MRI with lower field strength. Such effect, however, have not been reported so far for a 3T MRI. We report a case that exemplifies the possible detrimental effects of a 3 T MRI generated noise on the auditory system. Our patient underwent investigation of his chronic backache in a 3 T MRI unit and developed hearing loss and tinnitus post-MRI examination. Hearing assessment was done using pure tone audiogram, distortion product otoacoustic emission (DPOAE) and brainstem electrical response audiometry (BERA) which revealed a unilateral sensorineural hearing loss which recovered within 3 days. However the tinnitus persisted. This is possibly a case of temporary threshold shift following noise exposure. However a sudden sensorineural hearing loss remains the other possibility.